2011
DOI: 10.1259/dmfr/72527764
|View full text |Cite
|
Sign up to set email alerts
|

The role of maxillofacial radiologists in gunshot injuries: a hypothesized missile trajectory in two case reports

Abstract: Gunshot injuries are an emerging form of trauma that oral radiologists increasingly have to deal with. There are two main types of gunshot injuries: high-velocity and low-velocity bullet injuries. The outcome of high-velocity gunshot injury is usually fatal; however, a nonfatal low-velocity injury to the maxillofacial region is more likely to be encountered by the oral and maxillofacial radiologist. It is therefore important to up-to-date knowledge of ballistic science and its implications in the field of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A ballistic injury, caused by a firearm or by the sudden explosion of ammunition, is rarely neat, clean, and predictable: due to a significant soft tissue and bone loss from the impact, this type of facial trauma represents a challenge for reconstructive surgery and for the final aesthetic and functional rehabilitation [ 1 ]. The damage that a bullet creates is unpredictable, and the management in planning and reconstructing a traumatic defect requires a multi-step approach and a multidisciplinary team [ 2 , 3 , 4 ]. In addition to the extensive damages to both soft and hard tissues, gunshot wounds cause deleterious physical and psychiatric effects, representing a complex set of challenges for the maxillofacial surgeon, the oral surgeon, the prosthodontist, and, sometimes, for the psychologist or psychiatrist [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ballistic injury, caused by a firearm or by the sudden explosion of ammunition, is rarely neat, clean, and predictable: due to a significant soft tissue and bone loss from the impact, this type of facial trauma represents a challenge for reconstructive surgery and for the final aesthetic and functional rehabilitation [ 1 ]. The damage that a bullet creates is unpredictable, and the management in planning and reconstructing a traumatic defect requires a multi-step approach and a multidisciplinary team [ 2 , 3 , 4 ]. In addition to the extensive damages to both soft and hard tissues, gunshot wounds cause deleterious physical and psychiatric effects, representing a complex set of challenges for the maxillofacial surgeon, the oral surgeon, the prosthodontist, and, sometimes, for the psychologist or psychiatrist [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two-thirds of gunshot injuries are caused by a single gunshot wound, resulting in 11% mortality within 24 h after trauma [ 15 ]. Ballistic injuries are responsible for 2–6% of facial fractures [ 17 ]; indeed, head and neck are one of the most commonly affected areas: more than 50% of attempted suicides, 14% of assaults, and 12% of accidental injuries [ 2 , 10 ]. A retrospective review of nearly 4100 gunshot wounds observed that about 6% involved the face [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It helps objectify the trajectory of the bullet with multi-plane reconstructions, assess the intra-parenchyma lesions, fractures and splinters and thereby determine the prognosis [21]. In the facial skeleton, 3D and denta-scanner reconstructions are of great help in assessing the injuries [22]. Nevertheless, the conventional x-ray and the CT-scan do not allow for a precise determination of the calibre of the projectile due to the fungiform deformation, fragmentation and mushroom effect of certain lead bullets whose tips are crushed, thereby increasing their diameter [5].…”
Section: Discussionmentioning
confidence: 99%
“…According to Hough, "the only rule regarding the science of ballistics is that the bullet follows no rules" 8 . Thus, with regard to this type of injury, various factors that affect the physiopathology and extent of the trauma must be taken into account in each case, such as: caliber, composition, projectile velocity, shooting distance, angle of penetration, trajectory and direction of the transferred energy 3,[9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%